Taxonomic signatures of cause-specific mortality risk in human gut microbiome - Aaro Salosensaari (Nature Portfolio, 2021)
Gut microbiome composition has a role in health and disease. Here the authors show that microbiome signatures related to the Enterobacteriaceae family are associated with cause-specific mortality risk in a well phenotyped Finish population over a 15-year follow-up.